Understanding millennial perceptions of human and nonhuman brands. Issue 1 (18th October 2018) - ul Haq, Junaid; Bonn, Mark A.
Abstract : Purpose: The purpose of this paper is to obtain perceptions from three distinct millennial segments about human and nonhuman brands related to travel. Specifically, inter and intra relationships between human and nonhuman brand credibility and equity constructs were investigated. Design/methodology/approach: Three millennial generational segments representing 571 respondents familiar with human and nonhuman brands, were investigated to explore their human and nonhuman brand credibility and equity perceptual issues. Structural equation modeling was employed to test the study hypotheses. Multi-group analysis was used to observe group differences. Findings: Selected millennial segments were found to have differences in their behavior pertaining to human and nonhuman brand constructs. All hypotheses of the overall model were accepted. For group differences, a significant difference was observed. Gen Z was found to be different in emulating humans and their linked nonhuman brands when compared to both younger and older Gen Y segments. Research limitations/implications: Study findings contribute to the marketing and tourism branding literature, as do findings related to generational differences. Practical implications: The authors suggested implications for hospitality and tourism marketing professionals under the headings of emotional attachment, entertaining content, use of social media and exploring brands online. Implications including multicultural, brands with strong values and engaging with brands can be helpful for hospitality managers in attracting millennials. Social implications: Social implications suggest behavioral differences related to three sub-groups of generational cohorts involving millennials. Originality/value: This is the first study dedicated to observing millennial perceptions for human and nonhuman brands.